﻿Taxonomy, distribution and host plants of some southern European and North African Sawflies (Hymenoptera, Symphyta) - Andrew Liston (Contributions to Entomology, 2023)
New taxonomic, biological and faunistic data are presented for some species of sawflies occurring in southern Europe and North Africa. Pamphilius mediterraneus sp. nov. is described from Italy (Sicily). It belongs to the alternans sub-group of the alternans species group. Pristiphora omalos sp. nov. is described from Greece (Crete). It belongs to the depressa species group. New junior synonyms are Calameuta tazzekae Lacourt, 1991 of Calameuta gaullei (Konow, 1896), and Emphytus leucostomus Costa, 1890 of Allantus cingulatus (Scopoli, 1763). Periclista rufiventris Zombori, 1979 is moved from the subgenus Periclista to the subgenus Neocharactus. Ametastegia (Protemphytus) persica Khayrandish, Talebi & Blank, 2015 is recorded for the first time in Europe, from Italy (Sicily), and a key to West Palaearctic Protemphytus species provided. Allantus enslini (Forsius, 1918) is more widespread in southern Europe than previously recorded. An identification key distinguishes it from its closer West Palaearctic relatives. New hostplant records are for Halidamia affinis (Fallén, 1807) (Rubia peregrina), Janus compressus (Fabricius, 1793) (Sorbus torminalis), and Macrophya albicincta (Schrank, 1776) (Centranthus ruber). New distribution records are given for a few other species.